Aspects of a Categorization of the Concept "Personality" in the Professional Consciousness of Teachers - An Example from Belarus - Bylinskaya, Natalia V. (International Dialogues on Education Journal, 2020)
The article presents research into the concept of "personality" in the categorical grid of the consciousness of primary and secondary school teachers. The data obtained demonstrate the presence of an orientation in the teachers’ minds and activities towards the implementation of personality-oriented, humanistic models of learning. At the same time, the structure of the concept of "personality" revealed in the pedagogical consciousness is not cognitively complex and holistic. This determines the specific tasks of psychological education to clarify and enrich teachers’ perceptions of personality.